Comparison of synovial fluid IL-6 levels in post arthroscopic reconstruction of anterior cruciate ligament using press fit technique with BPTB graft versus bio-screw fixation - Parmeshwar, Siddharath S.; Raju, Putta Kempa; Nagaraj, Preetham; Kanakagiri, Sahana V.; Javaregowda, Purushotham V. (International Journal of Research in Orthopaedics, 2026)
Background: Anterior cruciate ligament (ACL) injury causes an increase in synovial fluid concentrations of inflammatory cytokines and biomarkers of cartilage breakdown. ACL reconstruction reinitiates an "inflammatory hit" that leads to an increase in these markers and chondral degeneration, and is prolonged. A study aimed at comparing the IL-6 levels in patients undergoing ACL reconstruction with the press-fit technique and bio-screw fixation at different intervals. Methods: A retrospective study of 60 subjects between 14 and 62 years with ACL tear were divided randomly into two groups, Group 1 and Group 2, undergoing arthroscopic ACL reconstruction using bio-screw fixation and press-fit technique (Implant-less), respectively. The synovial fluid levels of IL-6 were assessed in the affected knee at 3months, 6months and 12 months post-surgery. Tegner-Lysholm Knee Scores were also compared. Results: It was found that at 6 months, IL-6 levels in Group 2 (average 47±0.2 pg/ml) were lower compared to Group 1 (average of 148±0.7 pg/ml). And at 12 months, Group 2 had an average of 41±0.5 pg/ml and Group 1 had an average of 84±0.3 pg/ml. Tegner-Lysholm scores in both groups were similar at the end of 12 months. Conclusions: Press fit technique allows bone-to-bone healing and is devoid of problems associated with hardware fixation like biocompatibility, biodegradability, synovial reaction, chondral degeneration and tunnel enlargement, though clinical outcomes are similar.